Poplar / willow catkin-based flexible porous carbon tube as well as preparation method and application thereof
Poplar/willet catkins were pretreated by ethanol solvent thermal method and calcined to prepare flexible porous carbon tubes based on poplar/willet catkins, which solved the problems of high adsorbent costs and difficult recovery of porous carbon materials in water pollution control, and achieved efficient adsorption and circulation Utilization, suitable for large-scale production.
Patent Information
- Application Number
- CN202411251230.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-07
- Publication Date
- 2024-12-31
AI Technical Summary
The production cost of adsorbents in existing water pollution control is high and the adsorption efficiency is low. The chemical activators used in the preparation of porous carbon materials are corrosive, and the prepared particles are small and difficult to recycle, resulting in difficulty in large-scale production.
Poplar/cats-based flexible porous carbon tube was used to pretreat poplar/cats-based flexible porous carbon tubes by ethanol solvent thermal method, lignin was removed and calcined, and a poplar/cats-based flexible porous carbon tube with excellent adsorption performance was prepared, using its flexible and porous structure. Easy to recycle.
It has achieved efficient adsorption of water pollutants, has good recycling performance and reusability, reduces production costs, and avoids the corrosiveness of chemical activators, which is suitable for large-scale production.
Smart Images

Figure CN119218974A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water pollution control, and in particular to a poplar / willow catkin-based flexible porous carbon tube and a preparation method and application thereof. Background Art
[0002] Adsorption method is widely used in the adsorption and removal of dyes in water bodies due to its simple operation, good performance and no secondary pollution. At present, people have developed a series of adsorbents for the treatment of water pollution, such as graphene-based nanocomposites, metal organic framework-based materials, activated carbon, zeolite and resin adsorbents. However, due to the production cost and adsorption efficiency of adsorbents, the development and application of adsorbents have not been widely promoted. Therefore, the development of more economical, more effective and mass-produced adsorbents has always been a major demand in the field of water pollution treatment. Biomass carbon materials are environmentally friendly materials because they come from the natural environment and have a fibrous structure. At the same time, they have many advantages such as good chemical reaction stability, high specific surface area, good recycling stability, and a wide applicable temperature range. They have become excellent adsorbents.
[0003] Poplars and willows are widely distributed in my country due to their excellent greening properties. They are planted on a large scale for economic timber, shelterbelts, water and soil conservation, and environmental greening, and are closely related to the ecological environment and people's economic life. Because the conditions required for their growth are simple, the planting range of poplars / willows in my country continues to increase. However, every spring, poplars / willows will produce a large amount of poplar / willow catkins, and the drifting of poplar / willow catkins has an adverse effect on human health, mainly causing allergic reactions and respiratory diseases. In addition, the fibers of poplar / willow catkins are organic fibers with low ignition points, fast burning, and light texture. They are often attached to the surface of some objects and spread very quickly. A slight spark can easily cause a fire. First, there are many ignition factors, and prevention and control are difficult. Second, the spread speed is fast. Third, it is difficult to extinguish the fire. Therefore, the resource utilization of poplar / willow catkins can not only solve the problem of environmental pollution, but also prepare high-value-added biocarbon materials, which is an effective way to achieve high value of poplar / willow catkins.
[0004] Poplar / willow catkin fiber is mainly composed of cellulose, lignin and hemicellulose. It is a natural fiber with a high cellulose content. Its surface contains a large number of hydroxyl groups of biomass. Therefore, poplar / willow catkin fiber can be used as a raw material for preparing biomass carbon and is used in the field of adsorption. Because the performance of porous carbon materials depends on the number and specific surface area of their surface active sites. Therefore, biomass carbon materials are often pretreated. The pretreatment methods mainly include hydrothermal method, template method, chemical activation method and self-assembly method. The existing disclosed technology usually uses an activator to prepare porous biocarbon materials with large specific surface area. Common activators include KOH, NaOH, K2CO3, H3PO4, K2C2O4, ZnCl2 and other activators. The chemical activation method has the advantages of more controllable pore size, lower activation temperature and time, and porous carbon with larger specific surface area and pore volume. However, it also faces some challenges, such as the corrosiveness of chemicals, the need for cleaning and purification of activation equipment and the prepared activated carbon, and the fine particles after carbonization are in powder form and not easy to recycle, which brings difficulties to large-scale production. Therefore, it is necessary to propose a poplar / willow catkin-based flexible porous carbon tube with excellent adsorption performance and apply it in water pollution control to solve the above problems. Summary of the invention
[0005] Based on the above, the purpose of the present invention is to provide a poplar / willow catkin-based flexible porous carbon tube and its preparation method and application, which has excellent adsorption performance and solves the problem of water pollution.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a poplar / willow catkin-based flexible porous carbon tube comprises the following steps:
[0008] Crush, clean and dry the poplar / willow catkins to obtain pure poplar / willow catkins;
[0009] The pure poplar / willow catkins are pretreated by an ethanol solvothermal method to obtain delignified poplar / willow catkins;
[0010] The delignified poplar / willow catkins are pre-oxidized and calcined to obtain the poplar / willow catkin-based flexible porous carbon tubes.
[0011] As a preferred solution of the method for preparing poplar / willow catkin-based flexible porous carbon tubes, the poplar / willow catkins are dried at a temperature of 50-90° C. for 30-90 minutes.
[0012] As a preferred scheme for the preparation method of poplar / willow catkins-based flexible porous carbon tubes, when the pure poplar / willow catkins are pretreated by an ethanol solvothermal method, the specific process includes: adding pure poplar / willow catkins and ethanol into a reactor, sealing and heating the reaction, taking out and filtering to obtain pretreated poplar / willow catkins and lignin black liquor, washing the pretreated poplar / willow catkins with anhydrous ethanol, washing until the filtrate is clear, and obtaining delignified poplar / willow catkins.
[0013] As a preferred solution of the method for preparing poplar / willow catkin-based flexible porous carbon tubes, the liquid-to-solid ratio of the ethanol to the pure poplar / willow catkins is (15-120):1, and the concentration of the ethanol is 40-80%.
[0014] As a preferred solution of the method for preparing poplar / willow catkin-based flexible porous carbon tubes, during the sealed heating reaction, the reaction temperature is 150-230° C. and the reaction time is 0.5-3.5 h.
[0015] As a preferred scheme for the preparation method of poplar / willow catkins-based flexible porous carbon tubes, the delignified poplar / willow catkins pre-oxidation treatment specifically comprises: placing the delignified poplar / willow catkins in a porcelain boat, pre-oxidizing in a muffle furnace, transferring the porcelain boat cooled to room temperature to a tubular furnace, and calcining the reaction with an inert gas to obtain poplar / willow catkins-based flexible porous carbon tubes.
[0016] As a preferred solution of the method for preparing poplar / willow catkin-based flexible porous carbon tubes, the pre-oxidation conditions are: heating to 250-300° C. at a rate of 0.5-2° C. / min and keeping the temperature for 30-90 min.
[0017] As a preferred solution for the preparation of poplar / willow catkin-based flexible porous carbon tubes, the calcination reaction conditions are: passing an inert gas for 15-45 minutes, heating to 700-800°C at a rate of 3-6°C / min, and keeping warm for 30-90 minutes; the inert gas includes one of nitrogen and argon.
[0018] A poplar / willow catkin-based flexible porous carbon tube is prepared by any one of the preparation methods described above.
[0019] An application of a poplar / willow catkin-based flexible porous carbon tube, wherein the poplar / willow catkin-based flexible porous carbon tube is applied to the adsorption of water pollutants.
[0020] The beneficial effects of the present invention are:
[0021] The present invention provides a poplar / willow catkin-based flexible porous carbon tube and its preparation method and application. By studying the conditions for pretreating poplar / willow catkins by ethanol solvent thermal method, the optimal solid-liquid ratio, pretreatment temperature and pretreatment time are obtained. When the pretreatment mass is 3.5g, the pretreatment time is 2h and the pretreatment temperature is 200℃, the sample has the largest specific surface area of 517.764m 2 / g, and the poplar / willow catkin-based flexible porous carbon tubes prepared under this condition have the largest adsorption capacity for MB, which is 385.71 mg / g, and the adsorption capacity for RhB is also the largest, which is 133.27 mg / g; and the poplar / willow catkin-based porous carbon tubes have good recycling performance. The flexible porous tubes are not easy to break into powder due to their flexibility, and their porous tubular morphology is convenient for separation, recovery and recycling from water. After four cycles, the adsorption capacity for the dye Rhodamine B (RhB) is still relatively high, and the degradation rate after four adsorptions can still reach 89.43% or more, with good reusability, and can be used in water pollution control. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.
[0023] Figure 1 is the lignin dissolution rate of poplar fluff with different pretreatment qualities;
[0024] Figure 2 is the lignin dissolution rate of poplar fluff at different pretreatment times;
[0025] Figure 3 is the lignin dissolution rate of poplar fluff at different pretreatment temperatures;
[0026] Figure 4 IR spectra of poplar fluff, delignified poplar fluff and poplar fluff-based flexible porous carbon nanotubes, where (a) is original poplar fluff, (b) is delignified poplar fluff, and (c) is delignified poplar fluff-based flexible porous carbon nanotubes;
[0027] Figure 5 are the XRD patterns of original poplar fluff carbon (a) and delignified poplar fluff-based flexible porous carbon tubes (b);
[0028] Figure 6 This is the Raman spectrum of delignified poplar fluff-based flexible porous carbon tubes;
[0029] Figure 7 are SEM images of original poplar fluff (a, b) and delignified poplar fluff (c, d);
[0030] Figure 8 are SEM images of original poplar fluff carbon (a, b, c) and delignified poplar fluff-based flexible porous carbon tubes (d, e, f);
[0031] Fig. 9 This is the TEM image of delignified poplar fluff-based flexible porous carbon tubes;
[0032] Fig.10 These are the N2 adsorption-desorption curves and pore size distribution diagrams of poplar fluff porous carbon with different pretreatment qualities, where (a) is 0.5 g, (b) is 1 g, (c) is 1.5 g, (d) is 2 g, (e) is 2.5 g, (f) is 3 g, (g) is 3.5 g, and (h) is 4 g;
[0033] Fig.11 N2 adsorption-desorption curves and pore size distribution diagrams of poplar fluff-based flexible porous carbon tubes at different pretreatment times;
[0034] Fig.12 N2 adsorption-desorption curves and pore size distribution diagrams of poplar-based flexible porous carbon tubes at different pretreatment temperatures;
[0035] Fig.13 is the adsorption equilibrium curve of different dyes on the poplar-based flexible porous carbon tubes;
[0036] Fig.14 The adsorption performance of different dyes by poplar fluff-based flexible porous carbon tubes prepared by different pretreatment methods, wherein (a) is the adsorption performance of poplar fluff-based flexible porous carbon tubes prepared by different pretreatment times, and (b) is the adsorption performance of poplar fluff-based flexible porous carbon tubes prepared by different pretreatment temperatures;
[0037] Fig.15 is the adsorption kinetic curve of different dyes by poplar-based flexible porous carbon tubes;
[0038] Fig.16 are the fitting curves of the adsorption kinetics of different dyes by the poplar-based flexible porous carbon tubes, where (a) is the pseudo-first-order kinetic fitting curve and (b) is the pseudo-second-order kinetic fitting curve;
[0039] Fig.17 This is a graph showing the cyclic adsorption performance of poplar fluff-based flexible porous carbon tubes for RhB.
[0040] Fig.18 This is a flexibility test diagram of poplar fluff-based flexible porous carbon tubes. DETAILED DESCRIPTION
[0041] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0042] This embodiment provides a method for preparing a poplar-based flexible porous carbon tube, and the specific steps are as follows:
[0043] S100: crushing, washing and drying poplar fluff to obtain pure poplar fluff;
[0044] Specifically, the poplar fluff is cleaned with deionized water, and the drying temperature is 50-90°C for 30-90 min. The drying temperature can be set to 50°C, 60°C or 70°C, preferably 60°C, and the drying time can be set to 30 min, 60 min or 90 min, which is determined according to actual conditions.
[0045] S200: pure poplar fluff was pretreated by ethanol solvothermal method to obtain delignified poplar fluff;
[0046] Specifically, the specific process of pretreating pure poplar fluff by ethanol solvent thermal method includes: adding pure poplar fluff and ethanol into a reactor, sealing and heating the reactor for reaction, taking out and filtering to obtain pretreated poplar fluff and lignin black liquor, washing the pretreated poplar fluff with anhydrous ethanol, washing until the filtrate is clear, and obtaining delignified poplar fluff.
[0047] More specifically, the liquid-solid ratio of ethanol to pure poplar fluff is (15-120):1, and the ethanol concentration is 40-80%. The liquid-solid ratio of ethanol to pure poplar fluff can be set to 120:1, 60:1, 40:1, 30:1, 24:1, 20:1, 17:1 or 15:1, and the ethanol concentration can be set to 40% or 50% or 80%. During the sealed heating reaction, the reaction temperature is 150-230°C, and the reaction time is 0.5-3.5h. The reaction temperature can be set to 150°C or 190°C or 230°C, and the reaction time can be set to 0.5h or 2h or 3.5h, which is determined according to actual conditions.
[0048] S300: pre-oxidizing and calcining the delignified poplar fluff to obtain a poplar fluff-based flexible porous carbon tube.
[0049] Specifically, the specific process of pre-oxidation treatment of delignified poplar fluff includes: placing delignified poplar fluff into a porcelain boat, pre-oxidizing in a muffle furnace, transferring the porcelain boat cooled to room temperature to a tubular furnace, passing an inert gas to react, and obtaining poplar fluff-based flexible porous carbon tubes.
[0050] More specifically, the pre-oxidation reaction conditions are to heat the temperature to 250-300°C at a rate of 0.5-2°C / min and keep it warm for 30-90min. The specific setting is to heat the temperature to 250°C at a rate of 0.5°C / min and keep it warm for 90min, or to heat the temperature to 300°C at a rate of 2°C / min and keep it warm for 30min, or to heat the temperature to 270°C at a rate of 1°C / min and keep it warm for 60min; preferably, heat the temperature to 270°C at a rate of 1°C / min and keep it warm for 60min, which is determined according to the actual situation.
[0051] More specifically, the calcination reaction conditions are: reacting with an inert gas for 15-45 minutes, heating to 700-800°C at a rate of 3-6°C / min, and keeping warm for 30-90 minutes; specifically, reacting with an inert gas for 15 minutes, heating to 800°C at a rate of 3°C / min, and keeping warm for 90 minutes, or reacting with an inert gas for 45 minutes, heating to 700°C at a rate of 6°C / min, and keeping warm for 30 minutes, or reacting with an inert gas for 30 minutes, heating to 750°C at a rate of 5°C / min, and keeping warm for 60 minutes; preferably, reacting with an inert gas for 30 minutes, heating to 750°C at a rate of 5°C / min, and keeping warm for 60 minutes, which is determined according to actual conditions, wherein the inert gas includes one of nitrogen and argon.
[0052] The present invention will be further described below by means of specific examples.
[0053] Example 1
[0054] The poplar fluff was crushed, cleaned with deionized water, and dried at 60° C. to obtain clean poplar fluff.
[0055] Take 3.5g of poplar fluff and 60mL of 70% ethanol and add them to the reactor, quickly seal it, pre-treat it, place it in a 200℃ oven, take it out after reacting for 2h, and filter it to obtain the pre-treated poplar fluff fiber and lignin black liquor. Wash the pre-treated poplar fluff with anhydrous ethanol until the filtrate is clear. Dry and weigh the pre-treated poplar fluff after washing, and calculate the lignin removal rate.
[0056] The delignified poplar fluff was placed in a porcelain boat, pre-oxidized in a muffle furnace, heated to 270°C at a rate of 1°C / min, and kept warm for 60 minutes. The porcelain boat cooled to room temperature was transferred to a tubular furnace, and after nitrogen was passed for 30 minutes, the temperature was raised to 750°C at a rate of 5°C / min, and kept warm for 60 minutes. Finally, the poplar fluff-based flexible porous carbon tubes were obtained.
[0057] Example 2
[0058] The preparation process and reaction conditions were consistent with those of Example 1, wherein 0.5 g of poplar fluff was reacted with 60 mL of 70% ethanol, the liquid-to-solid ratio was 120:1, the pretreatment time was 3 h, and the temperature was 200°C.
[0059] Example 3
[0060] The preparation process and reaction conditions were consistent with those of Example 1, wherein 1 g of poplar fluff was reacted with 60 mL of 70% ethanol, the liquid-to-solid ratio was 60:1, the pretreatment time was 3 h, and the temperature was 200°C.
[0061] Example 4
[0062] The preparation process and reaction conditions were consistent with those of Example 1, wherein 1.5 g of poplar fluff was reacted with 60 mL of 45% ethanol, the liquid-to-solid ratio was 40:1, the pretreatment time was 3 h, and the temperature was 200°C.
[0063] Example 5
[0064] The preparation process and reaction conditions were consistent with those of Example 1, wherein 2 g of poplar fluff was reacted with 60 mL of 50% ethanol, the liquid-to-solid ratio was 30:1, the pretreatment time was 3 h, and the temperature was 200°C.
[0065] Example 6
[0066] The preparation process and reaction conditions were consistent with those of Example 1, wherein 2.5 g of poplar fluff was reacted with 60 mL of 70% ethanol, the liquid-to-solid ratio was 24:1, the pretreatment time was 3 h, and the temperature was 200°C.
[0067] Example 7
[0068] The preparation process and reaction conditions were consistent with those of Example 1, wherein 3 g of poplar fluff was reacted with 60 mL of 55% ethanol, the liquid-to-solid ratio was 20:1, the pretreatment time was 3 h, and the temperature was 200°C.
[0069] Example 8
[0070] The preparation process and reaction conditions were consistent with those of Example 1, wherein 3.5 g of poplar fluff was reacted with 60 mL of 60% ethanol, the liquid-to-solid ratio was 17:1, the pretreatment time was 3 h, and the temperature was 200°C.
[0071] Example 9
[0072] The preparation process and reaction conditions were consistent with those of Example 1, wherein 4 g of poplar fluff was reacted with 60 mL of 70% ethanol, the liquid-to-solid ratio was 15:1, the pretreatment time was 3 h, and the temperature was 200°C.
[0073] Example 10
[0074] The preparation process and reaction conditions were consistent with those of Example 1, wherein 3.5 g of poplar fluff was reacted with 60 mL of 70% ethanol, the liquid-to-solid ratio was 17:1, the pretreatment time was 1 h, and the temperature was 200°C.
[0075] Embodiment 11
[0076] The preparation process and reaction conditions were consistent with those of Example 1, wherein 3.5 g of poplar fluff was reacted with 60 mL of 75% ethanol, the liquid-to-solid ratio was 17:1, the pretreatment time was 2 h, and the temperature was 180°C.
[0077] Example 12
[0078] The preparation process and reaction conditions were consistent with those of Example 1, wherein 3.5 g of poplar fluff was reacted with 60 mL of 75% ethanol, the liquid-to-solid ratio was 17:1, the pretreatment time was 3 h, and the temperature was 220°C.
[0079] Example 13
[0080] The preparation process and reaction conditions were consistent with those of Example 1, wherein 3.5 g of poplar fluff was reacted with 60 mL of 70% ethanol, the liquid-to-solid ratio was 17:1, the pretreatment time was 0 h, and the temperature was 220°C.
[0081] Embodiment 14
[0082] The preparation process and reaction conditions were consistent with those of Example 1, wherein 3.5 g of catkins were reacted with 60 mL of 70% ethanol, the liquid-to-solid ratio was 17:1, the pretreatment time was 2 h, and the temperature was 200°C.
[0083] In order to illustrate the conditions for pretreatment of poplar fluff by ethanol solvothermal method and obtain the optimal solid-liquid ratio, pretreatment temperature and pretreatment time, an adsorption experiment was conducted on the poplar fluff-based flexible porous carbon tubes prepared in the above embodiment. The dye of the adsorption experiment was used as the adsorbate, and the prepared poplar fluff-based flexible porous carbon tubes were used as the adsorbent. The adsorption performance of the porous carbon material was evaluated by tests such as adsorption equilibrium curve, adsorption kinetic curve, and cyclic adsorption performance.
[0084] 1. Adsorption experiment
[0085] 1. Adsorption equilibrium experiment
[0086] In order to explore the adsorption performance of poplar fluff porous carbon materials on different dyes, the adsorption capacity of carbon fibers on dyes was used to express its adsorption performance. A series of dyes with different concentrations (100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, 600 mg / L) were prepared, 10 mg of poplar fluff-based flexible porous carbon tubes were accurately weighed, and placed in a conical flask together with 50 mL of a certain concentration of dye solution, sealed, and placed in a constant temperature oscillator at 25°C for 12 hours. After adsorption equilibrium, a certain amount of solution was taken, filtered with a water filter, and diluted, and its absorbance was measured. The maximum adsorption capacity of the porous carbon material on the dye was calculated by formula (2-1).
[0087]
[0088] Where Q e , C0, C e are the equilibrium adsorption amount of the porous carbon material to the dye (mg / g), initial concentration (mg / L), and equilibrium concentration at time t (mg / L); V is the volume of the solution (mL); m is the mass of the added porous carbon material (g).
[0089] 2. Adsorption kinetics experiment
[0090] Add 50mL of 600mg / L dye to a conical flask, weigh 10mg of poplar fluff-based flexible porous carbon tubes and put them into the conical flask. Place the conical flask in a 25℃ constant temperature oscillator and oscillate, taking samples at regular intervals. The sampling time is 1min, 2min, 5min, 10min, 15min, 20min, 30min, 60min, 120min, 240min, 480min. The adsorption equilibrium curve of the poplar fluff-based flexible porous carbon tubes for the dye is calculated by formula (2-2).
[0091]
[0092] Where Q t is the adsorption amount of porous carbon material at time t (mg / g); C0 is the initial concentration of dye (mg / L); C t is the concentration of the dye at time t (mg / L); V is the volume of the dye (mL); m is the mass of the added carbon fiber (g).
[0093] 3. Cyclic adsorption performance
[0094] In order to explore the reusability of poplar fluff-based flexible porous carbon tubes, an adsorption-desorption cycle experiment was carried out. 10 mg of porous carbon material was added to a conical flask containing 50 mL of 600 mg / LRhB dye and oscillated on a constant temperature oscillator at 25 ° C for 12 h. After the adsorption was completed, the sample was collected, repeatedly washed with deionized water and anhydrous ethanol until colorless, and then dried at 60 ° C. The dried carbon material was used for the next adsorption experiment. Repeat the above steps 4 times.
[0095] 4. Analysis of adsorption experimental results
[0096] (1) Lignin dissolution rate of poplar fluff with different pretreatment qualities
[0097] Table 1 and Figure 1 The experimental data of lignin dissolution rate of poplar fluff with different pretreatment qualities. Poplar fluff of different qualities was treated with ethanol solution in turn. As can be seen from Table 1, the lignin removal rate reached more than 50%, and it showed a trend of increasing first and then decreasing with the increase of poplar fluff pretreatment quality. When the pretreatment quality was 3.5g, the poplar fluff lignin removal rate reached the maximum, which was 51.81%. As the pretreatment quality continued to increase, the lignin removal rate decreased. It is speculated that when the pretreatment quality was low, the amount of ethanol in the solvent was large, and the relative amount of poplar fluff was small. Ethanol was easy to react with acetic acid produced by the self-catalysis of organic matter contained in the poplar fluff itself, which was not conducive to the catalytic cracking of lignin ether bonds in poplar fluff fibers, resulting in a decrease in the amount of lignin dissolved. When the mass of poplar fluff increased, the solvent was not in sufficient contact with the poplar fluff fibers, and the heat capacity of the ethanol solvent system was low, so the energy provided for the ether bond cracking of lignin in the poplar fluff fibers and the dissolution of lignin was small, resulting in a low lignin removal rate. Comprehensive analysis of the experimental results shows that 3.5g is the optimal pretreatment amount.
[0098] Table 1 Lignin dissolution rate of poplar fluff with different pretreatment qualities
[0099]
[0100] (2) Lignin dissolution rate of poplar fluff at different pretreatment times
[0101] From Table 2 and Figure 2 It can be seen that when the pretreatment mass is 3.5g, the lignin removal rate increases significantly with the increase of reaction time. The longer the pretreatment time, the greater the lignin dissolution rate, showing an upward trend. When the reaction time increases from 1h to 2h, the lignin removal rate increases by 20.34%, and when the reaction time increases from 2h to 3h, the removal rate increases by 11.46%. If the reaction time continues to increase, the amount of lignin dissolution will not change much. Considering the specific surface area results of the samples, 2h is the optimal pretreatment time.
[0102] Table 2 Lignin dissolution rate of poplar fluff at different pretreatment times
[0103]
[0104] (3) Lignin dissolution rate of poplar fluff at different pretreatment temperatures
[0105] From Table 3 and Figure 3 It can be seen that when the pretreatment mass is 3.5g and the pretreatment time is 2h, the lignin removal rate has been increasing with the increase of reaction temperature. When the reaction temperature is 180℃, the lignin removal rate is 38.71%. When the reaction temperature increases from 180℃ to 200℃, the lignin removal rate is 40.35%, an increase of 1.64%. When the reaction temperature increases from 200℃ to 220℃, the lignin removal rate is 63.43%, and the removal rate increases by 23.08%. The rate of increase of the removal rate increases. It is preliminarily inferred that when the temperature is low, the dissolution capacity of ethanol on lignin in poplar fluff is limited, and the change of temperature has little effect on the dissolution rate. When the temperature is high, the lignin in poplar fluff is dissolved under the combined action of ethanol solution and high temperature. The temperature has a greater effect on the dissolution rate of lignin. The higher the temperature, the greater the dissolution rate of lignin. Considering the BET results comprehensively, 200℃ is the optimal pretreatment temperature.
[0106] Table 3 Lignin dissolution rate in poplar fluff at different pretreatment temperatures
[0107]
[0108] 2. Related Characterization Analysis
[0109] The following characterization analysis was performed on the poplar / willow catkin-based flexible porous carbon tubes and raw materials prepared in the embodiments of the present invention to test their performance.
[0110] 1. IR analysis
[0111] IR was measured by Fourier transform infrared spectrometer. The measurement range was 4000~500cm -1 , pressed with KBr. IR can identify the organic functional groups on the surface of porous carbon materials to analyze the composition of carbon materials.
[0112] Depend on Figure 4 (a) It can be seen that 3420cm -1 The peak at 2920cm is the stretching vibration absorption peak of poplar fluff -OH; -1 The absorption peak of CH stretching vibration in poplar fluff is at 1730cm -1 Absorption peaks of stretching vibration of C=O carbonyl in poplar fluff; 1509, 1420 cm -1 The typical aromatic skeleton vibration of lignin is at 1433, 1460cm -1 The absorption peak of CH bending vibration is double peak; 1063cm -1The absorption peak is caused by the stretching vibration of CO bonds in cellulose. Compared with the original poplar fluff, Figure 4 (b) 1509, 1420 cm in delignified poplar fluff -1 The typical lignin aromatic skeleton vibration was significantly weakened, indicating that the lignin content in the poplar fiber tube was reduced and had been removed to a large extent by the ethanol solution. Figure 4 (c) is the infrared spectrum of delignified poplar fluff porous carbon at 3420 cm -1 The peaks at 1509 and 1420 cm -1 The aromatic skeleton vibration of lignin at 1063 cm -1 The absorption peak caused by the stretching vibration of CO bonds in cellulose almost disappears. It can be seen that most of the organic matter in poplar fluff fiber is removed after high-temperature calcination.
[0113] 2. XRD analysis
[0114] The crystal structure of the carbon material is detected by X-ray diffraction to determine the orderliness of the pore structure of the carbon material.
[0115] Figure 5 The XRD spectra of the original poplar fluff carbon and delignified poplar fluff carbon. As can be seen from the figure, both of them have obvious diffraction peaks at 23° and 43°, corresponding to the (002) and (100) crystal planes of graphite carbon, respectively, indicating that the obtained porous carbon material is an amorphous structure carbon with a certain microcrystalline structure. Compared with the original poplar fluff carbon, the degree of graphitization of delignified poplar fluff carbon did not change after carbonization, indicating that the removal of lignin did not change the order of poplar fluff carbon.
[0116] 3. Raman analysis
[0117] The samples were analyzed using a laser Raman tester, and the defect and graphitization degree of the carbon material were determined by the intensity ratio of the D peak and the G peak in the spectrum.
[0118] Figure 6 This is the Raman spectrum of delignified poplar fluff porous carbon. The porous carbon material has a Raman spectrum of 1337 cm -1 、1581cm -1 There are obvious absorption peaks at the positions corresponding to the disordered (D) peak and the graphite crystal (G) peak. The (D) peak is related to the defects and disorder of the carbon material, and the (G) peak is related to the graphitization degree, Sp 2 Hybridized carbon atoms are usually represented by R=I D / I G The value of I is used to characterize the graphitization degree of carbon materials. D / I GThe peak intensity ratio is 0.87, which is much smaller than 1. The lower peak intensity ratio proves that the porous carbon material has a high degree of graphitization, which is conducive to charge transfer. The combined analysis of XRD and Raman proves that the delignified poplar fluff porous carbon prepared in this paper is a community composed of disordered carbon and graphitized carbon, and the content of graphitized carbon is relatively high.
[0119] 4. SEM and TEM analysis
[0120] Figure 7 (a, b) are SEM images of original poplar fluff, and (c, d) are SEM images of poplar fluff without lignin. From (a, b), we can see that the poplar fluff fiber is a hollow tubular structure, the fiber is slender and has a certain length, the poplar fluff has a large tubular cavity, the fiber surface is smooth, its diameter reaches about 16μm, and the tube wall thickness is about 1.5μm. From (c, d), we can see that the poplar fluff fiber tube after delignification is obviously thinner, and the diameter is also reduced to about 10μm. There are holes on the fiber surface, indicating that ethanol has dissolved the lignin in the poplar fluff fiber tube after high temperature, leaving dissolution traces on the tube wall, and forming holes on the fiber tube surface.
[0121] Figure 8 SEM images showing poplar fluff carbon and its delignified poplar fluff-based flexible porous carbon tubes. Figure 8 It can be seen from (a, b, c) that the poplar fiber still has a good tubular structure after high-temperature calcination and carbonization. The carbon fiber surface is smooth and the diameter of the carbon fiber is significantly reduced by about 10μm. This is because the volatile components such as organic matter in the fiber are lost after high-temperature carbonization, causing the tube diameter to shrink. Figure 8 In (d, e, f), it can be clearly observed that the wall of the delignified poplar fluff porous carbon material is significantly thinner, the fiber structure is slightly deformed, the fiber surface is rough, and there are many holes, which is mainly the pore structure left by the dissolution of lignin. After high-temperature carbonization treatment, the fiber diameter shrinks and the tube wall is also significantly thinner, indicating that the ethanol solvothermal method successfully dissolves the lignin in the poplar fluff tube.
[0122] Fig. 9 This is a TEM image of a delignified poplar fluff-based flexible porous carbon tube. It can be clearly seen from the image that there are many etched holes on the poplar fluff fiber wall, indicating that the ethanol solvent heat treatment of the poplar fluff fiber has indeed dissolved the lignin in the poplar fluff fiber and formed a porous structure. This porous structure increases the contact area between the material and external substances, which is beneficial to improving the adsorption performance of the carbon material.
[0123] 5. BET Analysis
[0124] The specific surface area, pore size distribution and pore volume of carbon materials were determined by N2 adsorption and desorption.
[0125] (1) Different pretreatment quality of poplar fluff porous carbon
[0126] Fig.10 Table 4 shows the specific surface area and pore volume of porous carbon with different pretreatment qualities of poplar fluff. Fig.10 It can be seen that the adsorption and desorption curves of the poplar fluff porous carbon all belong to type IV isotherms, the curves are smooth, and hysteresis loops appear, indicating that the prepared porous carbon is a typical mesoporous material. The larger specific surface area is beneficial to its adsorption performance, and the adsorption performance can be used to remove pollutants in the water. With the increase of the pretreatment mass of poplar fluff, the specific surface area of the biochar also changes. It is speculated that when the pretreatment amount is small, the ethanol in the solution self-polymerizes. After self-polymerization, the ethanol concentration decreases and lignin cannot be effectively removed. As can be seen from the figure, when the pretreatment mass is 1g, the specific surface area of the porous carbon is the largest, which is 464.532m 2 / g, pore volume is 0.344cm 3 / g, the specific surface area is 463.244m when the pre-treated mass is 3.5g 2 / g, pore volume is 0.330cm 3 / g, the specific surface area of the two is not much different. When the pre-treated mass is 4g, the specific surface area is 402.017m 2 / g, pore volume is 0.266cm 3 Taking into account the experimental error and economic benefit, the pre-treated mass of poplar fluff is set to 3.5 g in the present invention.
[0127] Table 4 Physical properties of poplar fluff-based flexible porous carbon nanotubes prepared from poplar fluff with different pretreatment qualities
[0128]
[0129] (2) Poplar fluff-based flexible porous carbon nanotubes with different pretreatment times
[0130] Fig.11 Table 5 shows the specific surface area and pore volume of the porous carbon with different pretreatment times. Fig.11 It can be seen that the carbon fibers obtained after carbonization of untreated poplar fluff show an obvious hysteresis loop, and its specific surface area is about 86.329 m 2 / g, pore volume is 0.150cm 3 / g. The adsorption-desorption curve of the porous carbon with poplar fluff after ethanol solvent thermal treatment is a type IV isotherm. After 1h of pretreatment, its specific surface area is 484.54m 2 / g, pore volume is 0.367cm 3 / g. When the pretreatment time is 2h, the hysteresis loop is more obvious, which is a typical mesoporous material. The maximum specific surface area is more than 6 times that of the untreated carbon, which is 517.764m 2 / g, pore volume is 0.455cm3 / g, when the pretreatment time continued to increase to 3h, the specific surface area decreased to 463.244m 2 / g, pore volume is 0.330cm 3 / g. With the extension of time, the specific surface area of the poplar fluff porous carbon first increases and then decreases. It is speculated that with the extension of pretreatment time, the lignin in the poplar fluff fiber is gradually dissolved, and the lignin dissolves into holes on the surface of the fiber tube, which increases the specific surface area. With excessive lignin dissolution, the holes gradually become larger, and the excessively large holes will lead to a decrease in the specific surface area.
[0131] Table 5 Physical properties of poplar fluff-based flexible porous carbon nanotubes prepared at different pretreatment times
[0132]
[0133] (3) Poplar fluff-based flexible porous carbon nanotubes prepared at different pretreatment temperatures
[0134] Fig.12 Table 6 shows the specific surface area and pore volume of the poplar fluff-based flexible porous carbon tubes prepared at different pretreatment temperatures. Fig.12 It can be seen that the adsorption-desorption curves of the poplar-based flexible porous carbon nanotubes prepared at different pretreatment temperatures are type IV isotherms. When the pretreatment temperature is 180 °C, the specific surface area is 401.834 m 2 / g, pore volume is 0.252cm 3 / g, the hysteresis loop is more obvious when the pretreatment temperature is 200℃, which is a typical mesoporous material, and the specific surface area is the largest, which is 517.764m 2 / g, pore volume is 0.455cm 3 / g, when the pretreatment temperature continued to increase to 220℃, the specific surface area decreased to 404.59m 2 / g, pore volume is 0.288cm 3 / g, it is speculated that when the temperature is low, the ethanol solution has limited dissolution capacity for lignin, and lignin is dissolved on the surface of poplar fiber to increase its specific surface area. When the pretreatment temperature is high, the increase in temperature greatly accelerates the dissolution of lignin, resulting in excessive dissolution of lignin on the fiber surface, which not only destroys the tubular structure of poplar fiber, but also affects the formation of pores on the fiber surface, resulting in a decrease in specific surface area.
[0135] Table 6 Physical properties of poplar fluff-based flexible porous carbon nanotubes prepared at different pretreatment temperatures
[0136]
[0137] 3. Study on the adsorption properties of porous carbon materials
[0138] 1. Adsorption equilibrium curve
[0139] Fig.13 The following is the adsorption equilibrium curve of different dyes by delignified poplar fluff porous carbon material with a pretreatment mass of 3.5g, a pretreatment time of 2h, and a pretreatment temperature of 200℃. When the initial concentration of the dye increases, the equilibrium adsorption amount of poplar fluff fiber also gradually increases. The main reason is that when the concentration of the dye increases, the collision rate between the dye molecules and the carbon fiber increases, the number of effective collisions also increases, and the adsorption amount of the dye by the carbon fiber will also increase. When the initial concentration is 600mg / L, the equilibrium adsorption amount of the dye also reaches the maximum value. If the initial concentration of the dye is continued to increase, the equilibrium adsorption amount remains almost unchanged. The maximum adsorption amount of methylene blue (MB) is 385.21mg / g, rhodamine B (RhB) is 133.68mg / g, and methyl orange (MO) is 265.84mg / g. If the initial concentration of the dye is continued to increase, the equilibrium adsorption amount of the porous carbon tube to the dye remains almost unchanged. This is because when the amount of adsorbed dye reaches a certain amount, the adsorption will be in dynamic equilibrium, the dye molecules occupy the pores in the porous carbon material, and the dye molecules adsorbed on the carbon tubes will repel each other with the dye molecules in the solution, forming a dynamic equilibrium, so that the residual active sites on the carbon tubes and the tube surface cannot combine with the dye molecules, so the adsorption is in a saturated state.
[0140] 2. Adsorption experiment of poplar fluff-based flexible porous carbon tubes
[0141] In order to test the adsorption performance of different dyes on the poplar-based flexible porous carbon tubes prepared at different pretreatment times, Fig.14 (a) Poplar fluff-based flexible porous carbon tubes were used to adsorb 600 mg / L of different dyes. The pretreatment mass of the poplar fluff was 3.5 g, the pretreatment temperature was 200 °C, and the pretreatment time was set to 1 h, 2 h, and 3 h. Fig.14 As shown in (a), the adsorption of dyes is the largest when the pretreatment time of poplar fluff is 2h, MB is 385.21mg / g, RhB is 133.68mg / g, and MO is 265.84mg / g, which is consistent with the results of specific surface area. With the increase of pretreatment time, the adsorption of dyes by poplar fluff-based flexible porous carbon tubes first increases and then decreases. When the pretreatment time reaches 3h, the adsorption capacity of dyes decreases. With the extension of treatment time, the removal rate of lignin in poplar fluff by ethanol solution gradually increases, making the residual pores too large, resulting in a decrease in specific surface area, which is not conducive to the adsorption of dye molecules. When the pretreatment time of poplar fluff is 2h, the adsorption performance of poplar fluff-based flexible porous carbon tubes is the best.
[0142] Fig.14 (b) Poplar fluff-based flexible porous carbon tubes were used to adsorb 600 mg / L of different dyes. The pretreatment mass of the poplar fluff was 3.5 g, the pretreatment time was 2 h, and the pretreatment temperature of the poplar fluff was set at 180 °C, 200 °C, and 220 °C. Fig.14 As shown in (b), with the increase of pretreatment temperature, the adsorption of dyes by poplar fluff-based flexible porous carbon tubes first increases and then decreases. When the pretreatment temperature of poplar fluff is 200℃, the adsorption of dyes is the largest, MB is 385.21mg / g, RhB is 133.68mg / g, and MO is 265.84mg / g. When the pretreatment temperature reaches 220℃, the adsorption capacity of carbon fiber for dyes decreases. This is because the pretreatment temperature increases, the reaction of ethanol solution with some organic matter in poplar fluff at high temperature intensifies, and the removal rate of lignin in poplar fluff gradually increases, resulting in too large pores for dissolution, reducing the number of small pores, resulting in a decrease in specific surface area, which is not conducive to the adsorption of dye molecules. The above experimental results show that when the pretreatment mass of poplar fluff is 3.5g, the temperature is 200℃, and the time is 2h, the adsorption performance of poplar fluff-based flexible porous carbon tubes for dyes reaches the best, which is consistent with the results of specific surface area.
[0143] 3. Adsorption kinetics analysis of poplar fluff-based flexible porous carbon tubes
[0144] Since the diffusion process involved in adsorption includes internal diffusion and external diffusion, and internal diffusion is a relatively slow process, the time for adsorption to reach equilibrium is usually longer. At the same time, the contact time between the adsorbent and the dye has a great influence on the adsorption amount. In order to specifically determine the effect of adsorption time on the adsorption process of carbon fiber, different time nodes were set for sampling during the adsorption process. The adsorption experiment was carried out using poplar fluff-based flexible porous carbon tubes prepared with a pretreatment mass of 3.5g, a pretreatment time of 2h, and a pretreatment temperature of 200℃ as the adsorbent. The results are as follows Fig.15 As shown. When the poplar fluff-based flexible porous carbon tubes adsorb dyes, the adsorption rate is relatively high within 0-60 min. This is because the adsorption sites of the biomass carbon are not occupied by dye molecules at this time, and there are more active sites; between 60-240 min, the pores and functional groups on the biomass carbon are gradually occupied by dye molecules, the adsorption sites are reduced, and the adsorption rate gradually decreases. After 240 min, the adsorption gradually stabilizes until the adsorption basically reaches equilibrium after 480 min. Finally, the porous carbon material adsorbs 133.27 mg / g of RhB, 385.71 mg / g of MB, and 268.48 mg / g of MO. Fig.15 It can be seen that the poplar fluff-based flexible porous carbon tubes have the largest adsorption capacity for MB, followed by MO, and the smallest adsorption capacity for RhB. This may be because the molecules of RhB are larger and do not match the pore size of the porous carbon tubes, so the adsorption amount is small under the same specific surface area. This also shows that the poplar fluff-based flexible porous carbon tubes prepared by ethanol solvent thermal treatment in the present invention have a selective adsorption performance.
[0145] In order to explore the reaction mechanism of dye adsorption on poplar-based flexible porous carbon tubes, pseudo-first-order and pseudo-second-order kinetic models were used to fit the experimental data ( Fig.16 ). According to the fitting results, it is more accurate to use the pseudo-second-order kinetic model to fit the adsorption process. The adsorption process of the pseudo-second-order kinetic model is mainly a chemical reaction, which shows that in the process of adsorption of dyes by poplar-based flexible porous carbon tubes, chemical adsorption of the monolayer is the main adsorption mode. The dye molecules interact with the functional groups on the surface of the poplar-based flexible porous carbon tubes through chemical bonds, so that the dye molecules are adsorbed on the surface of the porous carbon material.
[0146] 4. Cyclic adsorption performance of poplar-based flexible porous carbon tubes
[0147] Fig.17 The experimental results of the cyclic adsorption-desorption of RhB by poplar fluff-based flexible porous carbon tubes. Compared with the initial adsorption capacity, the adsorption capacity of poplar fluff-based flexible porous carbon tubes decreased by 3.48% after one cyclic adsorption-desorption. Due to factors such as intermolecular forces, it is impossible for the dye to be 100% desorbed from the carbon fiber, resulting in some active sites still being occupied, which will also affect the adsorption amount after the cycle. Overall, after four cycles, the adsorption capacity of poplar fluff-based flexible porous carbon tubes for RhB was 105.43 mg / g, which is 89.43% of the initial adsorption capacity, indicating that the prepared poplar fluff-based flexible porous carbon tubes have excellent cyclic performance and can be used as an adsorbent in practical applications such as adsorption of residual organic dyes in water bodies.
[0148] 5. Flexibility test of poplar fluff-based flexible porous carbon tubes
[0149] Depend on Fig.18 It can be seen that the flexibility test of the poplar fluff-based flexible porous carbon tubes was carried out, a certain amount of poplar fluff-based flexible porous carbon tubes were placed in a cylindrical container, and then a 50g weight basically the same as the inner diameter of the cylindrical container was placed into the cylindrical container, and the height of the poplar fluff-based flexible porous carbon tubes in the cylindrical container was measured. After removing the 50g weight, the poplar fluff-based flexible porous carbon tubes can still restore the deformation to a certain height. Therefore, the poplar fluff-based flexible porous carbon tubes have a certain flexibility, are not easy to break into powder, and are easy to separate, recover and reuse from water.
[0150] In summary, the poplar fluff was pretreated with ethanol and its BET data were measured. The optimal pretreatment process was: pretreatment mass was 3.5 g, pretreatment time was 2 h, and pretreatment temperature was 200 °C. Under this condition, the sample had the largest specific surface area, which was 517.764 m 2 / g. At this time, the poplar fluff-based flexible porous carbon tube has the largest adsorption capacity for MB, which is 385.71 mg / g, and the adsorption capacity for RhB is also the largest, which is 133.27 mg / g; the poplar fluff porous carbon material has good recycling performance, and the adsorption capacity for RhB is still high after four cycles, and after four adsorptions, it still reaches 89.43% of the initial adsorption, with good reusability. At the same time, the poplar fluff-based flexible porous carbon tube has a certain flexibility, which is convenient for the poplar fluff-based flexible porous carbon tube to be separated, recovered and recycled from water.
[0151] In addition, the willow catkin-based flexible porous carbon tubes prepared in Example 14 have the same properties as the poplar catkin-based flexible porous carbon tubes, both of which have excellent adsorption capacity and recycling performance, and are used in the treatment of water pollution.
[0152] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for preparing a poplar / willow catkin-based flexible porous carbon tube, characterized in that: The following steps are involved: Crush, clean and dry the poplar / willow catkins to obtain pure poplar / willow catkins; The pure poplar / willow catkins are pretreated by an ethanol solvothermal method to obtain delignified poplar / willow catkins; The delignified poplar / willow catkins are pre-oxidized and calcined to obtain poplar / willow catkin-based porous carbon tubes.
2. The method for preparing poplar / willow catkin-based flexible porous carbon tubes according to claim 1, characterized in that: When the poplar / willow catkins are dried, the temperature is 50-90° C. and the time is 30-90 minutes.
3. The method for preparing poplar / willow catkin-based flexible porous carbon tubes according to claim 1, characterized in that: When the pure poplar / willow catkins are pretreated by the ethanol solvent thermal method, the specific process includes: adding pure poplar / willow catkins and ethanol into a reactor, sealing and heating for reaction, taking out and filtering to obtain pretreated poplar / willow catkins and lignin black liquor, washing the pretreated poplar / willow catkins with anhydrous ethanol, washing until the filtrate is clear, and obtaining delignified poplar / willow catkins.
4. The method for preparing poplar / willow catkin-based flexible porous carbon tubes according to claim 3, characterized in that: The liquid-to-solid ratio of the ethanol to the pure poplar / willow catkins is (15-120):1; the concentration of the ethanol is 40-80%.
5. The method for preparing poplar / willow catkin-based flexible porous carbon tubes according to claim 3, characterized in that: During the sealed heating reaction, the reaction temperature is 150-230° C. and the reaction time is 0.5-3.5 h.
6. The method for preparing poplar / willow catkin-based flexible porous carbon tubes according to claim 1, characterized in that: The specific process of the delignified poplar / willow catkin pre-oxidation treatment includes: placing the delignified poplar / willow catkin in a porcelain boat, pre-oxidizing in a muffle furnace, transferring the porcelain boat cooled to room temperature to a tubular furnace, and calcining with inert gas to obtain a poplar / willow catkin-based flexible porous carbon tube.
7. The method for preparing poplar / willow catkin-based flexible porous carbon tubes according to claim 6, characterized in that: The pre-oxidation conditions are: heating to 250-300° C. at a rate of 0.5-2° C. / min and keeping the temperature for 30-90 minutes.
8. The method for preparing poplar / willow catkin-based flexible porous carbon tubes according to claim 6, characterized in that: The calcination reaction conditions are: reacting with inert gas for 15-45 minutes, heating to 700-800° C. at a rate of 3-6° C. / min, and keeping the temperature for 30-90 minutes; the inert gas includes one of nitrogen and argon.
9. A poplar / willow catkin-based flexible porous carbon tube, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. The use of the poplar / willow catkin-based flexible porous carbon tube according to claim 9, characterized in that: The poplar / willow catkin-based flexible porous carbon tube is used for adsorption of water pollutants.